2008
DOI: 10.1029/2007wr006610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bedrock groundwater on spatial and temporal variations in soil mantle groundwater in a steep granitic headwater catchment

Abstract: [1] We investigated processes of soil mantle groundwater generation in a granitic headwater catchment in central Japan. Two types of groundwater were observed: ephemeral-type groundwater (EG), which developed in response to rainfall events and disappeared rapidly after the events ceased, and semiperennial-type groundwater (SPG), which remained formed for more than several months. The groundwater level, chemistry, and temperature within the soil and bedrock layers indicated that the source of EG was rain or soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 45 publications
(67 reference statements)
2
33
1
1
Order By: Relevance
“…They also commented that, while the seepage from bedrock might effectively determine the specific locations where debris flows might initiate, the distribution and connectivity of the near-surface bedrock fracture system are almost impossible to predict. Similar flows from bedrock into the overlying soil mantle are reported for steep granitic terrain by Katsura et al (2008).…”
Section: Preferential Flows and Landslidessupporting
confidence: 69%
“…They also commented that, while the seepage from bedrock might effectively determine the specific locations where debris flows might initiate, the distribution and connectivity of the near-surface bedrock fracture system are almost impossible to predict. Similar flows from bedrock into the overlying soil mantle are reported for steep granitic terrain by Katsura et al (2008).…”
Section: Preferential Flows and Landslidessupporting
confidence: 69%
“…Montgomery and Dietrich (2002) also noted the contribution of rapid lateral flow and slow bedrock flow to runoff generation in a small catchment. In headwater catchments, bedrock is important in controlling soil mantle groundwater generation and water flow processes (Katsura et al , 2008). Therefore, the weathering properties and resultant hydraulic properties of the soil and bedrock are more important than the geomorphic factors in small catchments.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that this characteristic is due to the large storage capacity of deeply weathered granite bedrock, the depth of which is more than 10 m in the middle of hillslope (Katsura et al, 2008). For example, Kosugi et al (2006) conducted hydrometrical observations at subcatchments within the KI, where they demonstrated that the saturated and unsaturated infiltration from soil to bedrock is a dominant hydrological process at the soil-bedrock interface and that the annual bedrock infiltration ranged from 35% to 55% of the annual precipitation.…”
Section: Runoff Mechanisms and Dependencies On Forest Disturbances Inmentioning
confidence: 97%
“…A dominant contribution of bedrock water has also been confirmed by end-member analysis using SiO 2 and H 2 SO 4 at KI (Katsuyama et al, 2005) and by the water pressure and temperature measurements at F2 . Recently, Katsura et al (2008) directly measured the temporal variations of bedrock groundwater and found that the baseline of the annual runoff variation was controlled by that of the bedrock groundwater on the hillslope. Because of the high weight of bedrock infiltration, stormflow is produced by water escaping from the infiltration in a granite hillslope.…”
Section: Runoff Mechanisms and Dependencies On Forest Disturbances Inmentioning
confidence: 99%